2007
DOI: 10.1152/ajplung.00140.2006
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular proteasome in the human alveolar space: a new housekeeping enzyme?

Abstract: We hypothesized that 20S proteasome is present and functional in the extracellular alveolar space in humans. Proteasomal activity was measured in bronchoalveolar lavage (BAL) supernatant from eight humans using specific proteasomal fluorogenic substrates and I 125 -albumin with and without specific proteasome inhibitors. Furthermore, gelfiltration, Western blot technique, and mass spectrometry were applied for proteasome characterization. All proteasomal fluorogenic substrates were hydrolyzed by BAL supernatan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
0
5

Year Published

2007
2007
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(42 citation statements)
references
References 67 publications
(41 reference statements)
1
36
0
5
Order By: Relevance
“…In a subsequent study, BALF from patients with ARDS was found to have increased proteasomal proteins compared with BALF from control subjects, but proteasomal activity was significantly decreased compared with healthy control subjects. In addition, ARDS BALF inhibited proteasome activity when mixed with BAL from healthy patients, suggesting the presence of a soluble inhibitor (41).…”
Section: The 26s Proteasome and Inhibitorsmentioning
confidence: 95%
“…In a subsequent study, BALF from patients with ARDS was found to have increased proteasomal proteins compared with BALF from control subjects, but proteasomal activity was significantly decreased compared with healthy control subjects. In addition, ARDS BALF inhibited proteasome activity when mixed with BAL from healthy patients, suggesting the presence of a soluble inhibitor (41).…”
Section: The 26s Proteasome and Inhibitorsmentioning
confidence: 95%
“…Moreover, the 20S proteasome can be released from the cell. Sixt et al [12] identified an extracellular and biologically active 20S proteasome in the human alveolar space. More importantly, Dutaund et al [13] applied an ELISA technique to detect the 20S proteasome in human serum.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, BAL supernatant successfully cleaved albumin in an ATP-and ubiquitin-independent manner. 81 These data point to the presence and biologic activity of proteasome in the alveolar space; furthermore, they imply a unique, ubiquitin-independent role for extracellular proteasome activity. The previous investigation could have profound implications on human pulmonary diseases, particularly those that involve an alveolar fi lling process that alters intraalveolar protein makeup or oncotic pressure.…”
Section: Extracellular Proteasome Function In Sepsis and Alimentioning
confidence: 88%
“…A small study illustrates the presence and activity of proteasome in the alveolar space. 81 All three proteasome activities were identifi ed in a cell-free supernatant of BAL fl uid and were inhibited by epoxomicin. Cell lysis was also ruled out as a potential source of alveolar proteasome.…”
Section: Extracellular Proteasome Function In Sepsis and Alimentioning
confidence: 99%